Physiological Responses of Contrasting Rice Genotypes to Salt Stress at Reproductive Stage - Gerona, Maria Elisa B.; Deocampo, Marjorie P.; Egdane, James A.; Ismail, Abdelbagi M.; Dionisio-Sese, Maribel L. (Elsevier, 2019)
Salinity is a major abiotic stress affecting plant growth and productivity. Considerable genetic variation is present in rice in response to salt stress, with higher sensitivity during early seedling and reproductive stage. In this study, physiological changes in leaves and developing panicles of rice genotypes (IR686, Sadri, Rc222, CSR28, IR670 and Pokkali) contrasting in salt tolerance at the reproductive stage were evaluated in greenhouse experiment under salt stress. The results showed that IR670 and the tolerant-check Pokkali maintained lower Na+/K+ ratio, less reduction in chlorophyll concentration, lower malondialdehyde (MDA) production, higher concentrations of reduced ascorbate (reduced AsA), higher proline accumulation and lower percentage reduction in pollen viability than the salt-sensitive genotypes under salt stress. The higher concentration of reduced AsA suggests an efficient ROS-scavenging system. Physiological measurements and pollen viability analysis revealed that Sadri (moderately tolerant at the seedling stage) is sensitive to salt stress at the flowering stage. The findings will be useful in breeding salt tolerant varieties at both seedling and reproductive stages by selecting appropriate genotypes and phenotypes